2012
DOI: 10.4314/ejesm.v5i3.9
|View full text |Cite
|
Sign up to set email alerts
|

The Fauna Biodiversity of Ikot Ondo Community Forest in Essien Udim L. G. A. of Akwa Ibom State, South Eastern Nigeria

Abstract: Prolonged deforestation, poaching and wildlife habitat loss has been a serious threat to wildlife conservation in Nigeria, thereby endangering fauna diversity resources in the country. This study was carried out to determine the population estimate of wild fauna in the communal land of Ikot Ondo Community forest in Essien Udim L. G. A. of Akwa Ibom State. The forest is situated in a rainforest ecosystem surrounded by villages whose source of livelihood is mainly through exploitation of the forest resources. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…It can also be attributed to selective exploitation (as evidenced in Mkpok forest) of these plant species which may have led to slow rate of regeneration and low ecological tolerance (Kabir et al, 2008). Furthermore, the species composition in the forests corroborates with the findings of (Onyekwelu et al, 2005;Ukpong et al, 2012;Udoakpan et al, 2013;Daniel et al, 2015 andJacob et al, 2015). These researchers reported that within the southern rainforests, a number of forest types can be recognized, some are rich in species of family Sterculiaceae, Moraceae, Meliaceae, Euphorbaceae, Mimosaceae (Fabaceae) and Apocynaceae with a middle storey of dense-crowned, wide-spreading trees and a ground flora that is mainly herbaceous and characterized by an abundance of creepers, mostly Acacia sp.…”
Section: Discussionsupporting
confidence: 68%
“…It can also be attributed to selective exploitation (as evidenced in Mkpok forest) of these plant species which may have led to slow rate of regeneration and low ecological tolerance (Kabir et al, 2008). Furthermore, the species composition in the forests corroborates with the findings of (Onyekwelu et al, 2005;Ukpong et al, 2012;Udoakpan et al, 2013;Daniel et al, 2015 andJacob et al, 2015). These researchers reported that within the southern rainforests, a number of forest types can be recognized, some are rich in species of family Sterculiaceae, Moraceae, Meliaceae, Euphorbaceae, Mimosaceae (Fabaceae) and Apocynaceae with a middle storey of dense-crowned, wide-spreading trees and a ground flora that is mainly herbaceous and characterized by an abundance of creepers, mostly Acacia sp.…”
Section: Discussionsupporting
confidence: 68%